Labranza mínima y su influencia en la productividad del cultivo de maní (Arachis hypogaea) en el Ecuador - Almache Aviles, Jenniffer Frinee (2022)
The document was developed with the theme of minimum tillage and its influence on the productivity of peanut (Arachis hypogaea) cultivation in Ecuador. It should be noted that the different types of tillage are conventional, or traditional, conservation, minimum or reduced, and direct sowing or zero tillage. Among the conclusions, it is determined that the decrease in crop yields is increasing due to soil degradation, due to overexploitation, high deforestation rates, the elimination of plant cover and excessive soil tillage; The increase in mechanized agricultural work coincides with the intention of the producers to increase the performance of their operations, resulting in increases in the number of passes of machines on the ground; mechanized tillage systems used in Ecuador resulted in considerably higher tillage erosion rates than previously reported for tillage implements in Europe and North America; the most used types of tillage are conventional, minimum, optimal, reduced, conservationist and direct sowing and in peanut cultivation, conventional tillage continues to obtain the best yields, due to the fact that farmers refuse to use another type of system; however, there are producers who do carry out minimum tillage. In addition, it is recommended to apply the minimum tillage method before planting and to preserve the organic matter of the soil and that it is beneficial for the development of peanut plants; train farmers on mechanized farming methods in peanut cultivation; carry out field trials in peanut cultivation, with various tillage methods and compare results and establish the zero tillage method in peanut cultivation to identify its agronomic behavior.